An Intelligent Cloud Computing Data Processing System for College Innovation and Entrepreneurship Data Statistics - Jia, Hongjun; Chen, Wenjing (Mobile information systems, 2022)
With the improvement of the enrollment rate in recent years, innovation and entrepreneurship in colleges and universities have become the focus of the country and people. However, the statistics of innovation and entrepreneurship in colleges and universities have become more and more complicated and difficult. The purpose of this paper is to study how to face the statistics of innovation and entrepreneurship in colleges and universities, then to study the intelligent cloud computing data processing system, and put forward the importance of innovation and entrepreneurship and cloud computing in colleges and universities. The experiment results show that it can be seen that the number of graduates has risen sharply from 2011 to 2020 and the percentage has risen from about 20% to about 90%, which has also led to a great increase in the difficulty of graduate entrepreneurial data management. The difficulty of graduate entrepreneurial data management has risen from around 18% at the beginning to around 87% in 2020. Therefore, it is necessary to study the data processing system to make data processing more efficient. The intelligent cloud computing data processing system significantly improves the quality and efficiency of entrepreneurial service management, and the data mining application in the system can also provide data support for the analysis and prediction of graduates’ entrepreneurial situations. The intelligent cloud computing data processing system significantly improves the quality and efficiency of entrepreneurial service management, and the data mining application in the system can also provide data support for the analysis and prediction of graduates’ entrepreneurial situations.